Замуж не напасть: [роман] / Лариса Кондрашова - Кондрашова Лариса (Русский романс, 2003)
Экземпляры: ф.3 (2003) / Инвентарный номер: 45641 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 64 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44